Determinants Related to Nutritional Status in the Elderly in Tongko Village, Lage District, Poso Regency - Anggri Alfira Yunitas Assa; Sabarulin Tarigan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Many elderly people in Indonesia experience nutritional disorders, namely those who are undernourished (BMI 16.5 – 18.49) as much as 31% and overnutrition as much as 1.8%. Undernutrition is associated with certain diseases and functional disorders, but little is known about its relationship to nutritional intake and nutritional care among the elderly..Objective : This study was to determine the factors related to the nutritional status of the elderly in Tongko Village, Lage District, Poso Regency. Research Methods: The research design used was descriptive analytic with a cross sectional approach. The population in this study were elderly people aged 60 years and over who were in Tongko Village, Lage District, Poso Regency. The sampling technique used purposive sampling with 49 elderly respondents. Data analysis was carried out univariate and bivariate using Chi Square test with a significance value of 5% alpha (α = 0.05). Result: this study shows that there is a relationship between knowledge and nutritional status in the elderly (p = 0.007), there is no relationship between attitudes and nutritional status in the elderly (p = 0, 090) and there is no relationship between family support and nutritional status in the elderly (p=0,365). Conclusion: that there is a relationship between knowledge and nutritional status in the elderly, there is no relationship between attitudes and nutritional status in the elderly and there is no relationship between family support and the nutritional status of the elderly. Suggestion: for the elderly to be willing to receive information in order to develop themselves to fulfill good nutrition.